Attenuation of organics contamination in polymers processing effluent using iron-based sludge process optimization and oxidation mechanism - Tony, Maha A (Environmental technology, 2022)
The feasibility of using iron extracted from acid mine drainage (AMD) as Fenton's reagent for removal of organics pollutants from polymer and plastics manufacturing effluent was investigated in this study. AMD iron dose, H2O2 concentration and pH were evaluated as the treatment factors for their effects on organics oxidation. Optimum treatment conditions were identified using response surface methodological analysis (RSM), and of the ranges of the treatment factors examined, an optimal treatment combination was found to be AMD iron concentration: 40 mg/L and H2O2: 500 mg/L at pH 2.2, organics removal efficiency as high as 98% for TOC removal was achieved. The removal efficiency increased with temperature up to 40°C and further temperature increases resulted in lower removal efficiencies. The organics oxidation was characterized well by investigating the kinetic order and the process is following the second-order reaction kinetics. The thermodynamic parameters showed that the oxidation reaction was endothermic and non-spontaneous in nature